Behavioral and Cardiometabolic Factors Associated with Prediabetes Among Adolescents - Nurul Anggini; Ilham Ilham; Ummi Kalsum (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Prediabetes among adolescents is an emerging public health problem due to its increasing prevalence and potential progression to type 2 diabetes mellitus. Various behavioral and cardiometabolic factors have been reported to contribute to the development of prediabetes; however, existing evidence remains fragmented. Objective: This study aimed to systematically review and synthesize current evidence regarding dietary, behavioral, obesity-related, and cardiometabolic factors associated with prediabetes among adolescents. Method: A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines. Literature searches were performed in PubMed, Scopus, ScienceDirect, and Google Scholar for studies published between 2021 and 2026. Eligible studies included original research involving adolescents aged 10–19 years and reporting factors associated with prediabetes, obesity, overweight, or related metabolic disorders. The methodological quality of the included studies was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist. Results and Discussion: A total of 11 studies met the eligibility criteria and were included in the review. The findings identified unhealthy dietary patterns, low physical activity, sedentary behavior, obesity, cardiometabolic abnormalities, and sugar-sweetened beverage consumption as factors associated with prediabetes among adolescents. Obesity emerged as the most consistent predictor of prediabetes, while behavioral factors such as junk food consumption, prolonged screen time, and inadequate physical activity contributed indirectly through increased obesity risk. Conclusion: Prediabetes among adolescents is influenced by multiple behavioral and cardiometabolic factors, with obesity serving as the primary intermediary determinant. Comprehensive interventions focusing on healthy dietary behaviors, physical activity promotion, obesity prevention, and early metabolic screening are essential to reduce the future burden of prediabetes and type 2 diabetes mellitus among adolescents